Subsurface evidence for late Mesozoic extension in western Mongolia: tectonic and petroleum systems implications. (24th May 2014) - Johnson, C. L.; Constenius, K. C.; Graham, S. A.; Mackey, G.; Menotti, T.; Payton, A.; Tully, J.
Abstract New seismic reflection profiles from the Tugrug basin in the Gobi‐Altai region of western Mongolia demonstrate the existence of preserved Mesozoic extensional basins by imaging listric normal faults, extensional growth strata, and partially inverted grabens. A core hole from this region recovered ca. 1600 continuous meters of Upper Jurassic – Lower Cretaceous (Kimmeridgian–Berriasian) strata overlying Late Triassic volcanic basement. The cored succession is dominated by lacustrine and marginal lacustrine deposits ranging from stratified lacustrine, to subaqueous fan and delta, to subaerial alluvial‐fluvial environments. Multiple unconformities are encountered, and these represent distinct phases in basin evolution including syn‐extensional deposition and basin inversion. Prospective petroleum source and reservoir intervals occur, and both fluid inclusions and oil staining in the core provide evidence of hydrocarbon migration. Ties to correlative outcrop sections underscore that, in general, this basin appears to share a similar tectono‐stratigraphic evolution with petroliferous rift basins in eastern Mongolia and China. Nevertheless, some interesting contrasts to these other basins are noted, including distinct sandstone provenance, less overburden, and younger (Neogene) inversion structures. The Tugrug basin occupies an important but perplexing paleogeographic position between late Mesozoic contractile and extensional provinces. Its formation may record a rapid temporal shift from orogenic crustal thickening to extensional collapse in the Late Jurassic, and/or an accommodation zone with a Mesozoic strike‐slip component.